Variation in neonate roe deer home range size - Öhman, Charlotte (SLU/Dept. of Ecology, 2017)
Home range determinants have been well-studied in many species, as is the case for adult roe deer. However, drivers of neonate roe deer home range size have not been covered in previous research. Earlier studies demonstrate a negative relationship between both increasing food availability and population density on adult roe deer home range size. Because neonate roe deer are highly dependent of their mothers during the first weeks of life, I expected that fawn home range size would be affected similarly by similar factors. It was also predicted that home range size and daily movements would be affected by fox density, temperature, year, fawn age, birth weight, sex, tick burden, and some mother qualities. Based on 91 radio-collared neonate roe deer (118 in movement analysis) and 12 adult females (14 in movement analysis) – comprising of 17 complete female-fawn relationships (23 in movement analysis), in two different study areas in south central and eastern Sweden, I show that, as expected, home range sizes of fawns and females were positively correlated. Moreover, neonate home range size and movements varied significantly between areas. The difference between the areas was partly explained by contrasting densities of which increasing abundances of both fox and roe deer caused smaller home ranges and shorter movements. Results are attributed to that both the increasing densities of roe deer and fox cause social constraints and avoidance behaviour, consequently decreasing both movements and home range size. This study is the first to determine the main drivers of neonate home range size and provides new knowledge of neonate roe deer spatial use encouraging for future studies based on these findings.